Gap Analysis Towards Service Quality in PT Djasa Sumatera - Komo, Reza Tiopan; Fachira, Ira (Journal of Business and Management, 2016)
Abstract. Freight forwarder industry has grown along with Indonesian’s needs to distribute products. In order to sustain in the industry, PT Djasa Sumatera has to evaluate its service so that they can improve it. The purpose of the research is to calculate the customer gap of PT. Djasa Sumatera through examination of the service quality dimensions. This study also intends to examine the customer gap and the impact of service quality dimensions toward the degree of customer satisfaction for PT. Djasa Sumatera. This study used quantitative approach by distributing a survey to 50 respondents of the PT Djasa Sumatera’s consumer in the first quarter of 2016. The respondents are the person who directly involved with PT Djasa Sumatera. The author adopted service quality dimensions for Business-to-Business to measure reliability, competence, consultative selling, credibility, price, responsiveness, geographical presence and tangibles as the dimension (Westbrook and Peterson, 1998). This study asses the customer expectation and customer perception to calculate the gap score. Findings show that there are gaps for all service dimensions is negative. [IF1] It means that the delivery service that has been provided by PT Djasa Sumatera is not in accordance to costumer’s expectation. The widest gap is credibility, also responsiveness dimensions has the highest expectation than the others. This means PT Djasa Sumatera could focus on these two dimensions to close the gap score. In the chapter five, the author made a recommendation for service improvement that can be pursued by PT Djasa SumateraKeywords : Service Quality, Business-to-Business, Freight Forwarder